Le monastère face aux laïques au haut Moyen Âge : lieux de culte secondaires et accueil aux limites de l’espace monastique dans le contexte italien - Eleonora Destefanis (Bulletin du Centre d’Études Médiévales d’Auxerre)
Hospitality for pauperes and peregrini represents a fundamental issue of the monastic life, involving both the material (food, lodging and health) and spiritual care. The study of the charity provided by monasteries is strongly connected with the definition of the monasterium, as in fact in written sources, is often linked to the word xenodochium; furthermore, the monasterium could reach boundaries much wider than the nucleous where monks live. Just at the edge of this space – the claustrum or a much bigger territory, perceived however as monasterium in every aspect – we can find specific complexes for social (and sometimes medical) services, in certain cases provided with secondary churches, distinct from the abbatial one.The paper studies, through some Early Middle Ages Italian cases and referring to written as well as archaeological sources, the topographical and functional choices connected to these structures. They appear sometimes thought for specific categories of people, such as women – who would not have had access to the claustrum in the male monasteries – or the distinguished guest, who, at least since the Carolingian Age, needed buildings provided with additional comfort.